Through the Ancient Sights of West Georgia - Dimitrov, Vladimir (Sledva : NBU Journal of Humanities and Arts, 2020)
A travelogue that combines modern pilgrimage with subtle observations of an art historian focused on the Christian Orthodox art and its astonishing monuments and relics in West Georgia.